THE ARGUMENTS AND REASONING ON THE IMMATERIALITY OF THE SOUL (TAJJARUD AL-NAFS) BASED ON MULLĀ ṢADRĀ’S PERSPECTIVE IN THE BOOK AL-SHAWĀHID AL-RUBŪBIYYAH - Mahyuddin, Mahyuddin; Rezaniya, Hamid Reza (Sekolah Tinggi Agama Islam Sadra, 2025)
This study examines the philosophical discourse of Mullā Ṣadrā on the immateriality of the soul (tajarrud al-nafs), with a focus on his seminal work, al-Shawāhid al-Rubūbiyyah. Mullā Ṣadrā, the founder of the transcendent philosophy (ḥikmah muta‘āliyah), developed a system rooted in foundational principles, including the primacy of existence (aṣālat al-wujūd), the gradation of existence (tashkīk al-wujūd), and substantial motion (ḥarakah jawhariyyah). His philosophical method integrates rational demonstration (burhān ‘aqlī), theology (kalām), Qur’anic insights, and mysticism (‘irfān), creating a unique and comprehensive framework. The research addresses a gap in the systematic analysis of Mullā Ṣadrā’s articulation of the soul’s immateriality in al-Shawāhid al-Rubūbiyyah, particularly within the third chapter (mashhad), where metaphysical principles intersect with discussions on the soul. Employing a descriptive, analytical, and argumentative methodology, the study identifies 14 structured arguments presented by Mullā Ṣadrā, evaluating their coherence and strength. Findings reveal that while many arguments are robust and deeply integrated into his philosophical system, others, particularly those based on textual and testimonial evidence, require refinement. These supplementary arguments serve to reinforce philosophical conviction rather than diminish logical validity. This research contributes to Islamic metaphysics by providing a focused analysis of al-Shawāhid al-Rubūbiyyah, offering insights into a relatively understudied text in Sadrian philosophy. It bridges classical Islamic thought with contemporary philosophical inquiry, highlighting the relevance of Mullā Ṣadrā’s views on the immaterial soul in understanding metaphysical anthropology and eschatology.